The problems in pediatric oncology. Cancer alterness: A review - Natalja A. Susuleva; Yulia E. Ryabukhina; Pervin A. Zeynalova; Marina I. Savelyeva (ZAO "Consilium Medicum", 2023)
One of the main problems in pediatrics and pediatric oncology is early diagnosis of malignancies in children. It makes a provision for high surveillance more than 90% and ability to restrict an anti-cancer treatment, which define a high quality of life with low incidence of acute reactions and complications of anti-cancer therapy especially delayed. At the same time, even today up to 75% of patients are check into a specialized hospital with advanced disease stages and large tumor mass. The main reason of it is the absence of cancer alterness in first patients contact doctors: pediatricians, highly specialized non-oncological doctors. Identification of high tumor risk children, knowledge of symptoms for differential diagnosis with oncological disorders, abidance by principium of cancer alterness, optimal patients logistics and teamwork of all doctors involved in patients with cancer are the recipe for successful treatment.